Dependencies and interdependencies: A theoretical comment - Wolfgang Bärtschi (Intereconomics, 1978)
In the area of foreign trade theory, the theorem of unequal exchange, in the area of social sciences in general and in the sphere of development policy in particular, the “dependencia“ approach, and in the politico-economic area, the interdependence approach, have yielded important results and — more important — may yield moe results. Those working on world models should try to integrate these results into their future research more effectively.
Keywords: 330; International Relations